Effect of Temperature on Heat Transfer Coefficient of Titanium Dioxide in Ethylene Glycol-based Nanofluid - Abdul Hamid, K.; Azmi, W. H.; R., Mamat; Usri, N. A.; G., Najafi (Faculty Mechanical Engineering, UMP, 2015)
Nanofluid as a coolant has potential for use in the heat transfer field because of its augmentation in thermal properties that offers advantages in heat transfer. Research on various working temperatures is still ongoing in the nanofluid field. This study focused on the effect of temperature on heat transfer behavior using titanium dioxide or TiO2 nanofluid as the working fluid in forced convection. The heat transfer coefficient was determined for flow in a circular tube under constant heat flux boundary conditions. The experiment was conducted with a Reynolds number less than 25000 with concentrations of TiO2 nanofluid at 0.5%, 1.0% and 1.5%. At 30oC, the maximum enhancement of 9.72% for 1.5% volume concentration was observed. Enhancements of 22.75% and 28.92% were found at 50oC and 70oC, respectively under similar nanofluid concentrations. The nanofluid performance was significantly influenced by working temperature. The heat transfer enhancement of TiO2 nanofluid was considerably improved at higher working temperature and high concentration because of the improvement of thermal properties.